The Effect of Service Quality on Customer Loyalty at the Bintang Makassar Store, Alauddin Branch - Syamsuryo Arjuna; Muh Nasrullah; Novayanti Sopia Rukmana (Public Resource Innovation Management and Excellence, 2024)
This study aims to determine how the description and influence of service quality on customer loyalty at Bintang Makassar store Alauddin Branch. To achieve this goal, the researchers used indicators to measure these variables. In the service quality variable, the indicators used are reliability, responsiveness, assurance, empathy, and physical evidence. As for the customer loyalty variable, the indicators used are repeat purchases, buying between product or service lines, referencing products to others, and showing immunity to competitors' attractiveness. In this study, the method used is quantitative method, with data collection techniques namely observation, questionnaires and documentation that are tested for validity and reliability. The sample used is purposive sampling technique with data analysis technique using SPSS program which consists of classical assumption test, linear regression test and determinant coefficient. The results showed that the indicators used for each variable showed that the description of service quality and customer loyalty at the Bintang Makassar store, Alauddin Branch was in the very good category. In addition, based on the results of simple linear regression and determinant coefficients, it is found that service quality has a significant effect on customer loyalty at the Bintang Branch Alauddin store.